2005
DOI: 10.1093/carcin/bgi371
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin mediates ceramide generation via the de novo pathway in colon cancer cells

Abstract: A wealth of evidence supports the notion that curcumin, a phytochemical present in turmeric, is a potent chemopreventive agent for colon cancer. Its mechanism of action remains incompletely understood. Here we report that curcumin's apoptosis-inducing effects in colon cancer cell lines are accompanied by robust ceramide generation. This occurs through de novo synthesis as the increase in ceramide could be attenuated by pre-incubation of the cells with myriocin, and no changes were observed in sphingomyelin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 19 publications
5
59
1
1
Order By: Relevance
“…Curcumin-induced apoptosis was also found to be associated with ROS generation in colon cancer (HT29 and HCT116) cells, hepatomas (Hep 3B and HepG2), submandibular carcinoma and a transformed human skin cancer cell line (COLO16). [6][7][8][9] Curcumin has been shown to generate ROS that resulted in mitochondrial DNA (mtDNA) damage in HepG2 cells. 10 Melanoma, along with cervical, prostate, lung and kidney cancer cell lines, exhibit resistance to the cytotoxic effects of curcumin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin-induced apoptosis was also found to be associated with ROS generation in colon cancer (HT29 and HCT116) cells, hepatomas (Hep 3B and HepG2), submandibular carcinoma and a transformed human skin cancer cell line (COLO16). [6][7][8][9] Curcumin has been shown to generate ROS that resulted in mitochondrial DNA (mtDNA) damage in HepG2 cells. 10 Melanoma, along with cervical, prostate, lung and kidney cancer cell lines, exhibit resistance to the cytotoxic effects of curcumin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These assemblies bear striking analogy with the helical polymers formed by DGK␦-SAM, which comprise six monomers per turn (23). Moreover, treatment of cells with curcumin, a drug known to deregulate ceramide and calcium levels in the ER (25,26), promotes formation of SMSr hexamers 4 ( Fig. 1).…”
mentioning
confidence: 90%
“…Curcumin Promotes meGFP-SMSr Homo-oligomerization in the ER-We recently observed that curcumin, a drug known to deregulate ceramide and calcium levels in the ER (25,26), promotes self-assembly of SMSr into hexamers. 4 Although this effect appears to be independent of fluctuations in ER ceramide or calcium levels and may potentially involve a curcumin-associated cross-linking activity (33), the underlying mechanism remains to be established.…”
Section: Self-assembly Of Megfp-smsr Into Er-resident Oligomers Is Crmentioning
confidence: 99%
“…Recently, the curcumin has been shown to induce ceramide generation to stimulate cancer cell apoptosis (Moussavi et al 2006). It seems that increasing agents of the intracellular ceramide levels could enhance tumor cell cytotoxicity and apoptosis caused by curcumin (Yu et al 2012).…”
Section: Th E Eff Ect Of C Longa and Curcumin On The Female Reproducmentioning
confidence: 99%